Pengaruh Kompensasi Finansial, Kompensasi Non Finansial dan Semangat Kerja terhadap Kinerja Karyawan PT. Pegadaian Kediri - Gandhes Putri Pamungkas; Lina Saptaria; Diana Ambarwati (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine and prove the influence of Financial Compensation, Non-Financial Compensation, and Work Morale on the Performance of Employees at PT. Pegadaian Kediri. This research uses a quantitative approach with data collected through purposive sampling, involving a sample of 44 employees of PT. Pegadaian Kediri. The analysis techniques employed include: the validity test, reliability test, normality test, multicollinearity test, linearity test, heteroscedasticity test, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and the R² coefficient of determination. Based on the study's results, Financial Compensation has a positive and significant partial effect on employee performance of PT. Pegadaian Kediri Sig 0.004 < 0.05. Non-Financial Compensation has a negative and insignificant effect on the performance of PT. Pegadaian Kediri, with a significance value of Sig 0.145 > 0.05. Work Morale has a positive and significant effect on the performance of PT. Pegadaian Kediri with a significance value of Sig 0.011 < 0.05. Simultaneously, Financial Compensation, Non-Financial Compensation, and Work Morale have a positive and significant effect on employee performance of PT. Pegadaian Kediri with a significance value of Sig 0.002 < 0.05.